International Comparative Studies in Mathematics Lessons for Improving Students' Learning - Cai, Jinfa; Mok, Ida A.C; Reddy, Vijay; Stacey, Kaye (ICME-13 Topical Surveys,, 2016)
It argues that the main purpose of educational research is to improve student learning, and that international comparative studies are no exception.